Latin‐American Special Olympics athletes: evaluation of oral health status, 2010. (7th March 2013) - Hanke‐Herrero, Rosana; López del Valle, Lydia M.; Sánchez, Carolina; Waldman, H. Barry; Perlman, Steven P.
ABSTRACT: Objectives: The purpose of this study was to evaluate the oral health status and dental needs of the athletes with intellectual disabilities from Latin‐American and Caribbean countries who were participating in the II Latin‐American Special Olympics games held in Puerto Rico, February 2010. Methods: There were 930 athletes who participated in the games, of whom 445 received a dental examination, including 367 from Latin‐American and 78 from Caribbean countries. Forty‐four trained and standardized dental professionals performed dental screenings of athletes with intellectual disabilities, following Special Olympic Special Smiles and CDC protocols. These criteria were used to record untreated caries, missing and filled teeth, and gingival status. Socio‐demographics, existence, and severity of pain and oral hygiene habits were assessed by questionnaire. Statistical analysis was performed using EPI‐INFO and SPSS Statistical Program to produce descriptive statistics and chi‐square test. Results: Untreated dental caries was recorded for more than half of the examined athletes. Missing teeth were noted in more than one‐third of the athletes. More than half of the participants had signs of gingival disease and half needed preventive mouth guards. Statistics for each Latin‐American country suggests a dissimilar trend of dental decay and treatment needs among nations. Conclusions: While the Special Olympic athletes may not be representative of the entire population of individuals with intellectual disabilities in their specific country, the general consistency of the oral health status of these athletes from the 31 countries supports the certainty of the need for increased dental services for individuals with intellectual disability in the respective countries.